Case Report: A case report of the diagnosis of renal inflammatory myofibroblastic tumor - Wu, Wenjie; Liang, Tiantian; Zhang, Hui (Frontiers in Oncology, 2025)
Renal inflammatory myofibroblastic tumor is a very rare disease that primarily occurs in the renal parenchyma and may even involve the renal pelvis. This study presents a case of renal inflammatory myofibroblastic tumor with exophytic growth, whose imaging appearance resembles that of a solitary perirenal mass. A 75-year-old male patient was referred to our hospital for further treatment after a retroperitoneal lesion was discovered and suspected at another hospital. Imaging examination revealed multiple cysts in both kidneys and a lesion located anterior to a cyst at the lower pole of the left kidney. Due to the presence of the cysts, the relationship between the lesion and the kidneys was unclear. We performed multiplanar reconstruction of the tumor images and generated a temporal signal curve. Based on these imaging findings, we determined that the lesion was a benign tumor of renal origin and could be surgically removed. Finally, pathological examination confirmed the diagnosis of a renal inflammatory myofibroblastic tumor. Postoperative telephone follow-up revealed that the patient was alive, and a follow-up abdominal CT performed at the local hospital showed no recurrence.